Polyethylene Glycol-grafted poly alpha-lipoic acid-dexamethasone nanoparticles for osteoarthritis - Cheng, Yuanqiang; Jing, Zheng; Xu, Yan; Sun, Lihui; Li, Dongbo; Liu, Jianguo; Li, Dongsong (Frontiers in Drug Delivery, 2023)
Osteoarthritis (OA) is a chronic inflammatory disease characterized by synovial hyperplasia, cartilage destruction and bone spur formation. Macrophages play an indispensable role in the pathogenesis of OA by producing proinflammatory cytokines. In traditional therapy, hormones can effectively inhibit the progression of inflammation by inhibiting the secretion of inflammatory cytokines by macrophages to achieve the effect of arthritis. However, the drug is quickly cleared from the joint space, high injection site infection rate and low local drug concentration make the clinical efficacy of corticosteroids greatly reduced. In this study, we reported the design and preparation of NPDXM/PPLA, elucidated the mechanism of action of NPDXM/PPLA in the treatment of OA in mice, and provided experimental basis for exploring the treatment of OA by polymer nanoparticles loaded with dexamethasone. We verified that NPDXM/PPLA could be well absorbed and released by macrophages by flow cytometry and confocal laser scanning microscopy., and it was found that NPDXM/PPLA could effectively reduce the proliferation of activated macrophages (RAW 264.7 cells). Enzyme-linked immunosorbent assay (ELISA) showed that NPDXM/PPLA could effectively reduce the expression of proinflammatory cytokines IL-1β, IL-6 and TNF-α. The knee bone structure of OA mice was evaluated by MicroCT, and it was found that intraarticular injection of NPDXM/PPLA effectively alleviated the bone damage of articular cartilage.Therefore, NPDXM/PPLA is a potential therapeutic nanomedicine for the treatment of OA.